Exogenous IBA stimulatory effects on root formation of Actinidia deliciosa rootstock and Actinidia arguta male scion stem cuttings - Sekhukhune, Mapogo Kgetjepe; Maila, Mmatshelo Yvonne (Frontiers in Sustainable Food Systems, 2024)
Recalcitrance to root of kiwifruit (Actinidia spp.) stem cuttings (SCs) is a restriction for its commercial production. Exogenous hormone is the key factor to regulate root formation, but the research on exogenous hormone stimulatory effects on Actinidia spp. is still lagging. Kiwifruit plants had been mostly propagated by seeds. However, vegetative propagation offers several advantages over sexual propagation, among them being crop homogeneity, practicability, and simplicity of the technique. A study was therefore conducted to investigate the potential responses of kiwifruit SCs from Actinidia deliciosa rootstock and Actinidia arguta male scion SCs treated with indole-3-butyric acid (IBA) concentrations at low (10, 100 ppm), medium (1,000, 10,000 ppm) and high (100,000 ppm) levels. Parallel experiments for A. deliciosa and A. arguta’s treatments were arranged in a randomized complete block design, with 12 replications. Treatments comprised different IBA concentrations, namely, 0 (control), 10, 100, 1,000, 10,000 and 100,000 ppm. At 103 days, rooting percentage, number of roots, root length, dry root mass, size of callus formation and callus percentage were determined. In A. deliciosa SCs, treatments had high significant (p ≤ 0.05) effects in rooting percentage, number of roots, root length, size of callus formation and callus percentage, except for dry root mass. In A. arguta male SCs, treatments also, showed high significant (p ≤ 0.05) effects in the number of roots, root length and dry root mass, except for the rooting percentage. No callus formation was observed in A. arguta male SCs. Relative to the control, in A. deliciosa SCs, the highest (42%) rooting percentage and lengthy (0.3 cm) roots, both were observed at the medium (10,000 ppm) IBA concentration, whereas the most (0.29) number of roots were produced at the highest (100,000 ppm) IBA concentration. Calli percentage (94%) was highest at low (100 ppm) IBA, while the biggest (2.8) size of callus formation was at the highest IBA concentration of 100,000 ppm, when compared to the control. In A. arguta male SCs, the greatest number of roots (1.08) and root mass (0.07 g) were attained at the medium IBA concentration of 10,000 ppm. The longest (0.94 cm) root length was achieved at the low IBA concentration of 100 ppm. The SCs of A. arguta male scion required low to medium (100 to 10,000 ppm) concentrations of IBA for proper roots stimulation and development, whereas in SCs of A. deliciosa, highest rooting percentage paired with callus formation, was achieved at medium to higher (10,000 to 100,000 ppm) IBA concentrations. Principal component analysis (PCA) revealed that PC1 and PC2 accounted for 99% of the entire variation. While PC1 accounted for 94% of the total variation, PC2 accounted for 5% of the total variation in A. deliciosa. However, in A. arguta PCA revealed that PC1 and PC2 accounted for 93% of the entire variation. While PC1 accounted for 72% of the total variation, PC2 accounted for 21% of the total variation. The use of exogenous application of IBA was effective for adventitious root formation in SCs of A. deliciosa rootstock and A. arguta male scion. IBA showed its effectiveness in stimulating root development at 10000 ppm IBA.